2021
DOI: 10.31234/osf.io/p4yb2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Accuracy and Validity of Self-Reported Social Media Use Measures Among Adolescents

Abstract: A growing number of studies have tried to assess the effects of social media on adolescents, who are among the most avid social media users. To establish the effects of social media use, we need accurate and valid instruments to measure adolescents’ time spent with these media. The aim of this preregistered study was to examine the accuracy and validity of retrospective surveys and experience sampling methods (ESM), by comparing adolescents’ responses to these self-report measures with their digital trace data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(79 reference statements)
2
18
0
Order By: Relevance
“…Several reviews have pointed at a need to move away from possibly biased self-report measures towards more objective measures of SMU use, such as log-based measures of time spent with SM. Indeed, self-report measures of time spent with SM correlate only moderately with similar log-based measures [42,43]. However, although log-based measures are often seen as the gold standard, they have their own validity threats, such as technical errors and the erroneous tracing of SM apps running in the background when the screen is turned off [42,43].…”
Section: Capturing the Content And Quality Of Social Media Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have pointed at a need to move away from possibly biased self-report measures towards more objective measures of SMU use, such as log-based measures of time spent with SM. Indeed, self-report measures of time spent with SM correlate only moderately with similar log-based measures [42,43]. However, although log-based measures are often seen as the gold standard, they have their own validity threats, such as technical errors and the erroneous tracing of SM apps running in the background when the screen is turned off [42,43].…”
Section: Capturing the Content And Quality Of Social Media Interactionsmentioning
confidence: 99%
“…Indeed, self-report measures of time spent with SM correlate only moderately with similar log-based measures [42,43]. However, although log-based measures are often seen as the gold standard, they have their own validity threats, such as technical errors and the erroneous tracing of SM apps running in the background when the screen is turned off [42,43]. This means that the modest correlations between self-reports and log-based measures could be due to validity issues of self-reports but also of objective measures.…”
Section: Capturing the Content And Quality Of Social Media Interactionsmentioning
confidence: 99%
“…Unsurprisingly, people's estimates of technology use are as problematic as other self-reports of behavior (Kaye et al, 2020). Whereas a handful of studies found underestimates (e.g., Ellis et al, 2019;Jones-Jang et al, 2020), other studies suggest that technology users overestimate how much time they spend with their devices and applications-be it the internet in general (Araujo et al, 2017;Scharkow, 2016), video games (Johannes, Vuorre, et al, 2021), SMS and calling (Boase & Ling, 2013;Vanden Abeele et al, 2013), smartphones (Sewall et al, 2020;Shaw et al, 2020), or social media (Verbeij et al, 2021). In a recent meta-analysis, Parry et al (2020) found substantial variation between studies in conclusions regarding under-or overestimates.…”
mentioning
confidence: 99%
“…For instance, one study reports that around 62.4% of the Vietnamese adults rely on social media as a source of news (Huynh et al, 2020 ), and around 67% of the U.S. adults at least occasionally get news on social media (Matsa and Shearer, 2018 ). Most Facebook users spend one or more hours per day on its platform (Ernala et al, 2020 , Figure 3), let alone the hours spent on other platforms like Instagram, WhatsApp, and Snapchat (e.g., Verbeij et al, 2021 ). Twitter, another important social media platform, has been used intensively by young adults (Antonakaki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%